2005
DOI: 10.1073/pnas.0501600102
|View full text |Cite
|
Sign up to set email alerts
|

Notch interferes with the scaffold function of JNK-interacting protein 1 to inhibit the JNK signaling pathway

Abstract: scaffold ͉ apoptosis ͉ glucose deprivation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 51 publications
3
69
1
Order By: Relevance
“…Cross-talk between different signaling pathways is a common phenomenon. APP and Notch signaling pathways interact at various points, including direct interactions of Notch and APP (15,40) or competition for binding proteins such as Fe65, Jip1 or Numb, which can physically associate with AICD and NICD (16,19,49). A recent report showed that NICD can repress AFT-mediated transcription by direct interaction (21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-talk between different signaling pathways is a common phenomenon. APP and Notch signaling pathways interact at various points, including direct interactions of Notch and APP (15,40) or competition for binding proteins such as Fe65, Jip1 or Numb, which can physically associate with AICD and NICD (16,19,49). A recent report showed that NICD can repress AFT-mediated transcription by direct interaction (21).…”
Section: Discussionmentioning
confidence: 99%
“…Both proteins undergo ectodomain shedding by the same α-secretases and regulated intramembrane proteolysis by γ-secretase complexes (13,29) leading to competition for these proteolytic cleavages (2) that are necessary for the translocation of the intracellular domains to the nucleus (N). Several adaptor proteins such as Fe65, Jip1 or numb can physically associate with AICD or NICD (3), thereby influencing their capacity of nuclear translocation and transcriptional activity (16,19,49). AICD is transported to the nucleus by Fe65 and together with Tip60 forms spherical nuclear AFT complexes (57) that represent transcription factories (TF).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest the existence of an activity of Notch receptor that is independent of its Su(H)/CBF-mediated transcriptional activity (Matsuno et al, 1997;Ramain et al, 2001;Endo et al, 2003;Nicolas et al, 2003;Hayward et al, 2005;Kim et al, 2005;Deregowski et al, 2006). In a welldocumented instance, Notch modulates Wnt signalling (Martinez and there is some evidence that the target of this activity is the effector of Wnt signalling Armadillo/␤-catenin (Nicolas et al, 2003;Hayward et al, 2005;Deregowski et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…JNK-deficient mice have been shown to exhibit aberrant T cell activation and differentiation (23)(24)(25). Recently, Kim et al (26) reported that the active form of Notch1 negatively regulates the JNK pathway by antagonizing JNK-interacting protein 1-mediated activation of JNK signaling. It has also been shown earlier (23) and again demonstrated in the present experiments that T cells exposed to Ag showed significant JNK induction (Fig.…”
Section: Notch3 Inhibition Does Not Affect Jnk Signaling In Myelin-rementioning
confidence: 99%